(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Arsha’s is one among the Astamahagada, and a commonest ano-rectal disease with a wide range of symptoms. It affects all economic groups of the population. In Ayurveda, Arsha’s is a growth of Mamsa with obstructs the anal opening. Anatomically anal canal is 51/2 Angula’s length. A faulty lifestyle and dietary habits along with occupational and physical stress triggers the pathology of Arsha’s. Doshic involvement includes Rakta along with Mamsa dhatu at Rakthavaha Dahmanis of Guda, which forms as Mamsa Ankura. Acharya Susrutha mentioned 4 curative measures for the treatment, they are Bhesaja, Kshara karma, Agni karma, Shastra karma. Hemorrhoids are dilated rectal veins. Thrombosed piles occur where there is high venous pressure, which is associated with severe pain, which hampers their daily routine, thereby they avoid defecation which leads to hardening of stool, constipation and rectal bleeding. The treatment includes the surgical excision of the thrombosed pile mass. A case study of thrombosed pile treated with Jaloukavacharana (leech therapy) has been recorded which has reduced the mass, pain, bleeding per rectum.